Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/15332640.2018.1484309
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward tobacco among low-income Hispanic adolescents: Implications for prevention

Abstract: Youth maintain several tensions in their views on tobacco. Tobacco use is considered unpleasant and harmful, yet youth perceive their peers to view it as cool. Peer to peer discussion of tobacco experiences and perceptions may help correct these incongruent viewpoints. Adding to this tension is the perception that tobacco is used to manage stress. Given the importance of the home environment for Hispanic youth, tobacco prevention efforts may benefit from engaging family to identify the ways in which tobacco us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Despite this, results relating to socioeconomic status were sparse. Only 17 out of 38 studies reported students' SES, six studies focused on participants mainly from deprived communities(26, 39,41,42,46,53) and only four studies assessed results separately according to school-level SES (31,48,49,61). These studies showed that context, in terms of school level SES, was reported to be important in both pre-and post-legislative data in terms of how social in uence on smoking behaviour was manifested.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite this, results relating to socioeconomic status were sparse. Only 17 out of 38 studies reported students' SES, six studies focused on participants mainly from deprived communities(26, 39,41,42,46,53) and only four studies assessed results separately according to school-level SES (31,48,49,61). These studies showed that context, in terms of school level SES, was reported to be important in both pre-and post-legislative data in terms of how social in uence on smoking behaviour was manifested.…”
Section: Discussionmentioning
confidence: 99%
“…This theme focuses on the higher level determinants which set the wider context and interact with the lower level determinants discussed in the subsequent four themes to affect smoking behaviour. Nineteen studies published before the introduction of comprehensive tobacco legislation contributed to this theme (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The main ndings within this theme centred around culture and socioeconomic status.…”
Section: [Insert Figure 3 Here]mentioning
confidence: 99%
See 3 more Smart Citations